Ewing's Sarcoma of the Frontal Bone with Intracranial Extension - Ahuja, Sana; Malik, Shaivy; Ahluwalia, Charanjeet (Journal of Neurological Surgery Reports, 2025)
Ewing's sarcoma, though rare, primarily affects children and young adults, commonly manifesting in long bones. Cranial involvement, particularly in the frontal bone, is exceptionally uncommon, posing diagnostic and therapeutic challenges. Meticulous pathological assessment is crucial for recognizing and managing such atypical presentations. A 16-year-old male presented with left frontal swelling and neurological symptoms. Imaging revealed a space-occupying lesion involving the left frontal bone with intracranial extension. Histopathology confirmed Ewing's sarcoma based on characteristic findings and positive immunohistochemical markers. Differential diagnoses include metastatic neuroblastoma, primitive neuroectodermal tumors, and chordomas, highlighting the importance of comprehensive evaluation. Ewing's sarcoma involving the skull necessitates a multidisciplinary approach for accurate diagnosis and management. This case underscores the significance of clinical, radiological, and pathological assessments in recognizing rare manifestations. Collaboration among teams is crucial for tailored management strategies and optimal patient outcomes.
Keywords: Ewing's sarcoma; frontal bone; intracranial; bone tumor